HPMA copolymer-bound doxorubicin induces immunogenic tumor cell death - Sirova, M; Kabesova, M; Kovar, L; Etrych, T; Strohalm, J; Ulbrich, K; Rihova, B (Current medicinal chemistry, 2013)
Treatment of murine EL4 T cell lymphoma with N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer conjugates of doxorubicin (Dox) leads to complete tumor regression and to the development of therapy-dependent longlasting cancer resistance. This phenomenon occurs with two types of Dox conjugates tested, despite differences in the covalent linkage of Dox to the polymer carrier. Such a cancer resistance cannot fully express in conventional treatment with free Dox, due to substantial immunotoxicity of the treatment, which was not observed in the polymer conjugates. In this study, calreticulin (CRT) translocation and high mobility group box-1 protein (HMGB1) release was observed in EL4 cells treated with a conjugate releasing Dox by a pH-dependent manner. As a result, the treated tumor cells were engulfed by dendritic cells (DC) in vitro, and induced their expression of CD80, CD86, and MHC II maturation markers. Conjugates with Dox bound via an amide bond only increased translocation of HSPs to the membrane, which led to an elevated phagocytosis but was not sufficient to induce increase of the maturation markers on DCs in vitro. Both types of conjugates induced engulfment of the target tumor cells in vivo, that was more intense than that seen with free Dox. It means that the induction of anti-tumor immunity documented upon treatment of EL4 lymphoma with HPMA-bound Dox conjugates does not rely solely on CRT-mediated cell death, but involves multiple mechanisms.
Keywords: Drug Resistance, Neoplasm; antigeny CD80; Polymethacrylic Acids; Phagocytosis; B7-2 Antigen; Doxorubicin; Mice, Inbred C57BL; B7-1 Antigen; Animals; protinádorové látky; kyseliny polymethakrylové; Dendritic Cells; antigeny CD86; Calreticulin; Mice; myši inbrední C57BL; Lymphoma, T-Cell; Antineoplastic Agents; doxorubicin; proteiny teplotního šoku; lymfom T-buněčný; Hydrogen-Ion Concentration; protein HMGB1; koncentrace vodíkových iontů; HMGB1 Protein; Heat-Shock Proteins; dendritické buňky; Cell Line, Tumor; nosiče léků; nádorové buněčné linie; zvířata; kalretikulin; apoptóza; fagocytóza; Drug Carriers; Apoptosis; chemorezistence; myši